The Impact of Public Leadership on Accountability in Local Government: Evidence from Indonesia - Setyaningsih, Titik; Indra Bastian; Choirunnisa Arifa; Fuad Rakhman (Universitas Muhammadiyah Surakarta, 2025)
This study examines the influence of public leadership on local government accountability. The study employed a survey methodology, involving local government employees in seven local governments in Central Java. The data analysis was conducted using Partial Least Squares. The research results indicate that rule-following leadership has a significant positive effect on accountability and financial reporting quality. Accountability leadership plays an important role in increasing financial reporting quality. An increase in financial reporting quality can increase accountability in an organization.